Pemberdayaan Ekonomi Masyarakat melalui Budidaya Jamur Tiram sebagai Media Dakwah Transformatif di Desa Mekarmanik - Dina Nafa Dilla Rachmatsyah; Siti Novieta Aisyah; Fika Aulia; Nazwa Putri Septiani; Muhammad Zidan Ramdani (CV. ITTC INDONESIA, 2026)
Limited economic opportunities and the need for sustainable community-based empowerment remain important challenges in strengthening financial independence and social resilience, particularly in rural communities. Productive economic activities integrated with religious values can become an alternative approach to improving community welfare while strengthening social and spiritual development. This community service program aims to describe and analyze economic empowerment through oyster mushroom cultivation as a medium of da'wah (Islamic outreach) in Mekarmanik Village. The program employed a participatory and collaborative approach involving preliminary surveys, socialization, technical training, mentoring, and evaluation activities. Data were collected through observation, interviews, and documentation, and analyzed using a descriptive qualitative approach. The results show that the program improved participants’ knowledge and skills in oyster mushroom cultivation, including baglog preparation, maintenance, harvesting, and basic marketing practices. The activity also contributed to economic empowerment by creating additional income opportunities and strengthening cooperation among community members. Furthermore, the integration of cultivation activities with religious guidance encouraged greater participation in worship activities, Islamic learning groups, and the development of values such as discipline, responsibility, and social solidarity. These findings indicate that oyster mushroom cultivation can function not only as an economic empowerment strategy but also as a transformative da'wah medium that supports community independence and spiritual development.